Visible and Solar Light Degradation of Ciprofloxacin and Norfloxacin using Titania Nanocomposite - M, Vijayatha; B, Vijayalaxmi; Md, Sajeeda; B, Ravali; K, Venkatesham; M, Kalpana; B, Padma; Aytam, Hari Padmasri (Asian Journal of Chemistry, 2023)
A simple sol-gel approach was used to synthesize TiO2 nanoparticles and its composite TiO2-PEG (TPG) using polyethylene glycol (PEG). The synthesized samples were characterized by XRD, SEM -EDX, TEM, UV-DRS, photoluminescence, Raman, XPS and BET-surface area techniques. The development of non-toxic, cost-effective, biocompatible and efficient polymeric nanocomposite increases the mechanical, thermophysical and physico-chemical properties of prepared nanomaterials. PEG affected the reaction with the crystallization process of the prepared titania nanoparticles to a great extent. The antibiotics ciprofloxacin and norfloxacin of fluoroquinolone class are widely used to treat certain bacterial infections and at the same time their residues generate serious health issues due to the lack of proper waste water treatment systems thus causing environmental pollution. The present study is thus focused on synthesizing efficient titania PEG nanocomposite to enhance the photocatalytic degradation of antibiotics in both solar and visible light. Efficiency of degradation was achieved maximum upto 74% with TPG and 64% with pure TiO2 nanoparticles for ciprofloxacin in visible light, similarly the degradation of norfloxacin was achieved 65% with TPG and 57% with TiO2 nanoparticles. Sunlight irradiation resulted in the degradation of ciprofloxacin to 80.2% with TPG and 77% with TiO2 nanoparticles whereas it was 78.7% with TPG and 68.6% with TiO2 nanoparticles for the degradation of norfloxacin. These results indicate that the catalyst TPG showed higher activity in presence of solar and visible light than TiO2 nanoparticles. Recyclability was also studied showing the stability of the photocatalyst used even after five successive runs.